Respuesta :

For this case we have the following functions:
 g (x) = 3 ^ x + 1
 f (x) = 3x + 1
 We observe that the graph of both functions are cut in the value of:
 x = 1
 Therefore, the value of the functions is the same for that value of x.
 Let's check it: g (1) = 3 ^ 1 + 1 = 3 + 1 = 4
 f (1) = 3 (1) + 1 = 3 + 1 = 4
 Answer:
 
ƒ (x) = g (x) is a true statement for:
 x = 1

Answer:

1

Explanation:

g(x) = 3^x + 1      and             f(x) = 3x +1

For 0;

g(0) = 3^0 + 1       and             f(0) = 3(0) + 1

g(0) = 1 + 1                               f(0) = 1

g(0) = 2                                    

Which is false.

For 1;

g(1) = 3^1 + 1       and               f(1) = 3(1) + 1

g(1) = 3 + 1                               f(1) = 3 + 1

g(1) = 4                                    f(1) = 4

Which is true.

For 2;

g(2) = 3^2 + 1       and              f(2) = 3(2) + 1

g(2) = 9 + 1                               f(2) = 6 + 1

g(2) = 10                                    f(2) = 7

Which is false.

For 3;

g(3) = 3^3 + 1       and              f(2) = 3(3) + 1

g(3) = 27 + 1                               f(2) = 9 + 1

g(3) = 28                                    f(2) = 10

Which is false.

Therefore, only 1 is the true answer.